Reading Asser in early medieval Wales: the evidence of Armes Prydein Vawr. (26th April 2019) - Thomas, Rebecca; Callander, David
Abstract: This article examines the connections between Asser's Life of King Alfred and the tenthcentury Welsh poem Armes Prydein Vawr . It studies the use of the place-name Santwic 'Sandwich' in Armes Prydein, and presents evidence that this form derives from a written source. An investigation of the sources containing this place-name before the late tenth century raises the distinct possibility that Asser's Life was the source drawn upon by the Welsh poet. Examination of the context in which Sandwich occurs in Asser and Armes Prydein highlights striking similarities in usage, strengthening the argument for a connection between the two texts. Further correspondences between these works are noted before discussing the potential implications of this new finding for our understanding of Asser (and his reception) and Armes Prydein more generally.